2022
DOI: 10.3390/electronics11213631
|View full text |Cite
|
Sign up to set email alerts
|

Developing Cross-Domain Host-Based Intrusion Detection

Abstract: Digital transformation has continued to have a remarkable impact on industries, creating new possibilities and improving the performance of existing ones. Recently, we have seen more deployments of cyber-physical systems and the Internet of Things (IoT) as in no other time. However, cybersecurity is often an afterthought in the design and implementation of many systems; therefore, there usually is an introduction of new attack surfaces as new systems and applications are being deployed. Machine learning has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Research studies have indicated that SVM and DT are among the most promising methods for anomaly detection. SVM and DT algorithms have been widely used in HIDSs due to their effectiveness in detecting and classifying intrusions [29][30][31]. In the context of HIDSs, SVM can learn the patterns and characteristics of known attacks and identify similar patterns in real-time system behavior, enabling the detection of unknown or novel attacks [29].…”
Section: Methods Description Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies have indicated that SVM and DT are among the most promising methods for anomaly detection. SVM and DT algorithms have been widely used in HIDSs due to their effectiveness in detecting and classifying intrusions [29][30][31]. In the context of HIDSs, SVM can learn the patterns and characteristics of known attacks and identify similar patterns in real-time system behavior, enabling the detection of unknown or novel attacks [29].…”
Section: Methods Description Limitationsmentioning
confidence: 99%
“…For almost two decades, researchers working in the field of intrusion detection have been using a publicly available Linux-based KDD98 data set [34][35][36]. However, that database is from 1998 and has lost its completeness and quality.…”
Section: Analysis Of Applicable Datasets For Malware Intrusion Detectionmentioning
confidence: 99%